Preparation method of material with photoelectric coupling catalytic performance
By forming P-N heterojunction in alginate aerogel, the problems of low efficiency and high cost in high-salt organic wastewater treatment are solved, and efficient photoelectrocatalytic oxidation and degradation effect is achieved.
Patent Information
- Application Number
- CN202311141586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
The prior art has problems of low efficiency, high cost and complex processes when treating high-salt organic wastewater. In particular, TiO2 nanotubes have weak electrocatalytic activity, and traditional electrode materials are costly and difficult to apply on a large scale.
Alginate hydrogel was generated by the replacement reaction of ferric nitrate, zinc nitrate and sodium alginate. Alginate aerogel was modified by freeze-drying method, and the carbon framework was calcined to form, and TiO2 was modified by hydrothermal method to form P-N heterojunctions, thereby improving photoelectrocatalytic activity.
It realizes efficient oxidation and degradation of organic pollutants in high-salt wastewater, reduces preparation cost and process complexity, improves the conductivity and porous structure of the material, and enhances the photoelectrocatalytic performance.
Smart Images

Figure HDA0004433640620000011 
Figure HDA0004433640620000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wastewater treatment, and specifically relates to a method for preparing a material with photoelectric coupling catalytic performance, and application of the material in treating high-salt organic wastewater. Background Art
[0002] High-salt wastewater comes from a wide range of sources. With the rapid development of industries such as chemical, pharmaceutical, and printing and dyeing, the amount of high-salt wastewater to be treated has also increased year by year. The composition of high-salt wastewater is complex and the difficulty of treatment is relatively high. Traditional wastewater treatment methods mainly include biological methods, physical and chemical methods, and a combination of the two, but traditional methods have obvious shortcomings in the treatment of high-salt wastewater. The disadvantage of biological treatment is that high concentrations of salt substances have an inhibitory effect on microorganisms, and the treatment effect is not ideal; the disadvantage of physical and chemical treatment is that the plan requires large investment, high operating costs, and it is difficult to achieve the expected purification effect. Therefore, finding and improving treatment technologies and processes for high-salt wastewater remains a focus of research at home and abroad.
[0003] In recent years, advanced oxidation technology has become one of the effective methods for treating organic wastewater. Advanced oxidation technology mainly includes electrocatalytic oxidation technology, photocatalytic oxidation technology and photoelectric coupled catalytic oxidation technology. Photocatalytic oxidation technology has the advantages of small secondary pollution, low operation difficulty and good degradation performance. 2 The material is a typical N-type semiconductor. Under light conditions, the electrons in the valence band gain energy and transition to the conduction band. Free electrons are generated in the conduction band, showing the electrochemical properties of the semiconductor. Therefore, it is widely used in the degradation of organic pollutants. However, in the process of photocatalytic degradation of organic matter, due to the 2 Nanotubes have only weak electrocatalytic activity in degrading organic pollutants. The applied voltage is only used to promote the separation of photogenerated electrons and holes. 2 Nanotubes only act as photocatalysts, and their electrocatalytic effect is poor. Electrocatalytic oxidation technology is another advanced oxidation technology with great application potential. Electrode material is a key factor in determining treatment efficiency. The earliest and most commonly used graphite electrode is inexpensive, but its mechanical strength and catalytic oxidation ability for organic matter are poor, and its oxygen evolution potential and current efficiency are low. Diamond electrodes have wide electrochemical windows, low background currents, high chemical stability, and low adsorption characteristics, but their preparation costs are too high, limiting their application in water treatment.
[0004] Patent publication number CN200810103518.2 discloses a method involving N-type TiO 2 BDD-TiO with PN junction characteristics 2 electrode, further improving the electrocatalytic activity of the BDD electrode and TiO 2The photoelectrocatalytic activity of the electrode is improved, and the quantum yield and service life of the electrode are increased. However, it still has disadvantages such as high preparation cost and complicated preparation steps. Therefore, it is necessary to develop a photoelectrocatalyst with simple method, controllable cost and excellent performance, so as to achieve efficient oxidation degradation of high-salinity wastewater through effective mediation of photoelectrocatalytic synergy. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a material with photoelectric coupling catalytic performance and a preparation method thereof. The catalytic material can be used as an anode in a photoelectric coupling reactor to selectively catalyze and oxidize the organic pollutants in high-salt wastewater.
[0006] The present invention provides a material with photoelectric coupling catalytic performance and a preparation method thereof, wherein alginate hydrogel is generated by a replacement reaction between iron nitrate and zinc nitrate and sodium alginate, and alginate aerogel is prepared by freeze drying. After calcination, a carbon skeleton with an aerogel structure is formed, which has good conductivity and rich porous structure. 2 The iron nitrate and zinc nitrate attached to the aerogel are calcined in an environment to generate P-type semiconductor zinc oxide and iron oxide; 2 Forming a PN heterojunction greatly improves the TiO 2 The number and oxidizability of the surface photogenerated holes. At the same time, TiO was modified by hydrothermal method. 2 The formation of nanotubes increases the TiO 2 The large specific surface area and loading on the aerogel are beneficial to the exposure of photogenerated holes and their contact and catalytic reaction with pollutants and salt ions.
[0007] The technical solution of the present invention is summarized as follows:
[0008] S1, preparing a 2wt% to 5wt% alginate aqueous solution;
[0009] S2, mixing a zinc salt solution having a molar concentration of 0.03 to 0.06 mol / L and an iron salt solution having a molar concentration of 0.03 to 0.06 mol / L in a volume ratio of 1:5 to 5:1 to form a precursor solution;
[0010] S3, slowly dripping the prepared alginate aqueous solution into the precursor solution, and continuously stirring to make it evenly dispersed;
[0011] S4, pouring the mixed solution after stirring evenly into a mold and standing it at 10-40° C. for 24-48 hours to form a cross-linked alginate hydrogel;
[0012] S5, washing the surface of the alginate hydrogel with deionized water and freeze-drying it at -40 to 80°C to obtain alginate aerogel;
[0013] S6, calcining the alginate aerogel at 300-500° C. for 6-10 hours in a nitrogen, argon or neon atmosphere to obtain a carbonized alginate aerogel having a porous three-dimensional structure;
[0014] S7, hydrothermal modification of TiO 2 , so that the modified TiO 2 In-situ deposition loading onto the surface of carbonized alginate aerogel;
[0015] S8, washing the material obtained in the previous step twice with a corresponding dilute acid solution with a molar volume of 0.1-05 mol / L, then washing it three times with deionized water, and then drying it at 80-100° C. for 12-24 hours to obtain the material with photoelectric coupling catalytic performance.
[0016] Among them, the zinc salt solution and the iron salt solution described in step S2 have the same anion type, including zinc nitrate solution and ferric nitrate solution, zinc chloride solution and ferric chloride solution, zinc sulfate solution and ferric sulfate solution, and zinc acetate solution and ferric acetate solution; the dilute acid solution described in step S7 includes dilute nitric acid, dilute hydrochloric acid, dilute sulfuric acid or dilute acetic acid, corresponding to the anion types of the zinc salt solution and the iron salt solution described in S2.
[0017] TiO modified by hydrothermal method 2 The specific steps are: TiO 2 The mixture is added into a sodium hydroxide solution with a molar concentration of 10-20 mol / L and mixed evenly. The mixed solution and the carbonized aerogel are poured into a hydrothermal reactor and reacted at 150-200° C. for 24-48 hours.
[0018] Preferably, the molar concentration of the ferric nitrate and zinc nitrate solutions used to prepare the precursor solution is 0.03-0.06 mol / L, and the volume ratio of the ferric nitrate and zinc nitrate solutions is 1:2-2:1.
[0019] Preferably, the alginate includes sodium alginate, potassium alginate, calcium alginate or magnesium alginate. Further preferably, the alginate can be sodium alginate.
[0020] Preferably, the zinc salt and iron salt include zinc nitrate and iron nitrate, zinc chloride and iron chloride, zinc sulfate and iron sulfate or zinc acetate and iron acetate, and the dilute acid solution described in S8 includes dilute nitric acid, dilute hydrochloric acid, dilute sulfuric acid or dilute acetic acid, corresponding to the anion type of the metal salt used. And when the metal salt is sulfate, the alginate cannot use calcium alginate. Further preferably, the zinc salt and iron salt can be selected from zinc nitrate and iron nitrate, and the dilute acid solution can be selected from dilute nitric acid.
[0021] Preferably, hydrothermal modification of TiO 2 The amount of TiO 2It is titanium dioxide P25, and the input amount is 3-10g / L.
[0022] The beneficial effects of the present invention are as follows:
[0023] The present invention provides a material with photoelectric coupling catalytic performance and a preparation method thereof. The raw materials used in the process of the present invention are cheap and easy to obtain. Alginate can be extracted from seaweed that is widely present in nature. Iron salts, zinc salts and titanium dioxide P25 are all mature chemical products, which is conducive to large-scale production. The material base uses carbonized alginate aerogel, which has a porous structure and rich functional groups on the surface, which is conducive to the adsorption and degradation of pollutants. The good electrical conductivity is conducive to the transfer of photogenerated carriers and the conduction of electrons in electrochemistry. At the same time, the excess zinc nitrate and iron nitrate on the surface decompose at high temperature to produce P-type semiconductor zinc oxide and iron oxide, respectively, which react with TiO 2 The formation of a PN heterojunction greatly increases the number and oxidizability of photogenerated holes on the titanium dioxide surface. Secondly, the presence of an electric field in the reactor causes anions such as Cl- to be enriched at the anode and oxidized by photogenerated holes on the anode surface into active substances such as Cl·, which are used to oxidize organic pollutants. By changing the voltage to control the electrochemical oxidation potential, the byproducts of salt ion free radical oxidation are reduced and the effective cycle of Cl- / Cl· is promoted. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a graph showing the COD variation of pollutants catalytically degraded by the photoelectric coupling material prepared in Examples 1 to 4 of the present invention in combination with comparative experiments.
[0025] Figure 2 This is a diagram showing the salinity variation of pollutants catalytically degraded by the photoelectric coupling material prepared in Examples 1 to 4 of the present invention in combination with comparative experiments. DETAILED DESCRIPTION
[0026] The present invention is described below by specific embodiments. Unless otherwise specified, the technical means used in the present invention are methods known to those skilled in the art. In addition, the embodiments should be understood as illustrative rather than limiting the scope of the present invention, and the essence and scope of the present invention are limited only by the claims. For those skilled in the art, without departing from the essence and scope of the present invention, these embodiments are subjected to several equivalent transformations and substitutions, and these equivalent transformations and substitutions should also be deemed to belong to the protection scope of the present invention.
[0027] Embodiment 1:
[0028] In this embodiment, the specific preparation method of the photoelectric coupling catalytic material is as follows:
[0029] (1) Dissolve 3 mmol of ferric nitrate and 3 mmol of zinc nitrate in 100 mL of deionized water and stir for 30 min; weigh 2 g of sodium alginate and disperse it in 100 mL of deionized water, slowly drip it into the ferric nitrate and zinc nitrate precursor solutions using a disposable syringe, pour it into a mold and let it stand at room temperature for 24 h to form a cross-linked alginate hydrogel.
[0030] (2) The hydrogel was removed from the mold and the surface was rinsed with deionized water, and then freeze-dried at -40°C for 12 h to obtain alginate aerogel.
[0031] (3) The aerogel was heated in N 2 After calcination at 300°C for 6 hours in an ambient environment, alginate aerogel with a porous three-dimensional structure was obtained after carbonization.
[0032] (4) Take 0.3 g of titanium dioxide P25 and add it to 100 mL of sodium hydroxide solution with a concentration of 10 mol / L and mix them evenly. Pour the mixed solution and the carbonized aerogel into a hydrothermal reactor. Place the hydrothermal reactor in a constant temperature oil bath and react at 150°C for 24 hours. Rinse it twice with 0.1 mol / L dilute nitric acid, rinse it three times with deionized water, and then dry it at 80°C for 12 hours to obtain a photoelectric coupling catalytic material.
[0033] The catalytic material is placed as follows: the photoelectric coupling catalytic material is placed in a photoelectric coupling reactor as an anode material, with the titanium dioxide surface facing the ultraviolet light, and 1L of high-salt organic wastewater with a salinity of 40ppt and a COD content of 5000mg / L is added to the reactor. The power of the photoelectric coupling reactor is turned on, and the reaction is carried out for 60 minutes. The water sample is taken out to detect the remaining COD content and salinity changes.
[0034] Embodiment 2:
[0035] In this embodiment, the specific preparation method of the photoelectric coupling catalytic material is as follows:
[0036] (1) Dissolve 4 mmol of ferric nitrate and 4 mmol of zinc nitrate in 100 mL of deionized water and stir for 30 min; weigh 3 g of sodium alginate and disperse it in 100 mL of deionized water, slowly drip it into the ferric nitrate and zinc nitrate precursor solutions using a disposable syringe, pour it into a mold and let it stand at room temperature for 24 h to form a cross-linked alginate hydrogel.
[0037] (2) The hydrogel was removed from the mold and the surface was rinsed with deionized water, and then freeze-dried at -40°C for 12 h to obtain alginate aerogel.
[0038] (3) The aerogel was heated in N 2 After calcination at 400°C for 6 hours in an ambient environment, alginate aerogel with a porous three-dimensional structure was obtained after carbonization.
[0039] (4) 0.4 g of titanium dioxide P25 was added to 100 mL of sodium hydroxide solution with a concentration of 10 mol / L and mixed evenly. The mixed solution and the carbonized aerogel were poured into a hydrothermal reactor. The hydrothermal reactor was placed in a constant temperature oil bath and reacted at 150° C. for 24 h. The reaction was then rinsed twice with 0.1 mol / L dilute nitric acid, rinsed three times with deionized water, and dried at 80° C. for 12 h to obtain a photoelectric coupling catalytic material.
[0040] The catalytic material is placed as follows: the photoelectric coupling catalytic material is placed in a photoelectric coupling reactor as an anode material, with the titanium dioxide surface facing the ultraviolet light, and 1L of high-salt organic wastewater with a salinity of 40ppt and a COD content of 5000mg / L is added to the reactor. The power of the photoelectric coupling reactor is turned on, and the reaction is carried out for 60 minutes. The water sample is taken out to detect the remaining COD content and salinity changes.
[0041] Embodiment 3:
[0042] In this embodiment, the specific preparation method of the photoelectric coupling catalytic material is as follows:
[0043] (1) Dissolve 4 mmol of ferric nitrate and 4 mmol of zinc nitrate in 100 mL of deionized water and stir for 30 min; weigh 5 g of sodium alginate and disperse it in 100 mL of deionized water, slowly drip it into the ferric nitrate and zinc nitrate precursor solutions using a disposable syringe, pour it into a mold and let it stand at room temperature for 24 h to form a cross-linked alginate hydrogel.
[0044] (2) The hydrogel was removed from the mold and the surface was rinsed with deionized water, and then freeze-dried at -40°C for 12 h to obtain alginate aerogel.
[0045] (3) The aerogel was heated in N 2 After calcination at 500°C for 8 hours in an ambient environment, alginate aerogel with a porous three-dimensional structure was obtained after carbonization.
[0046] (4) Take 0.5g of titanium dioxide P25 and add it to 100mL of sodium hydroxide solution with a concentration of 10mol / L and mix them evenly. Pour the mixed solution and the carbonized aerogel into a hydrothermal reactor. Place the hydrothermal reactor in a constant temperature oil bath and react at 150°C for 24h. Rinse it twice with 0.1mol / L dilute nitric acid, rinse it three times with deionized water, and then dry it at 80°C for 12h to obtain a photoelectric coupling catalytic material.
[0047] The catalytic material is placed as follows: the photoelectric coupling catalytic material is placed in a photoelectric coupling reactor as an anode material, with the titanium dioxide surface facing the ultraviolet light, and 1L of high-salt organic wastewater with a salinity of 40ppt and a COD content of 5000mg / L is added to the reactor. The power of the photoelectric coupling reactor is turned on, and the reaction is carried out for 60 minutes. The water sample is taken out to detect the remaining COD content and salinity changes.
[0048] Embodiment 4:
[0049] In this embodiment, the specific preparation method of the photoelectric coupling catalytic material is as follows:
[0050] (1) Dissolve 5 mmol of ferric nitrate and 5 mmol of zinc nitrate in 100 mL of deionized water and stir for 30 min; weigh 7.5 g of sodium alginate and disperse it in 150 mL of deionized water, slowly drip it into the ferric nitrate and zinc nitrate precursor solutions using a disposable syringe, pour it into a mold and let it stand at room temperature for 24 h to form a cross-linked alginate hydrogel.
[0051] (2) The hydrogel was removed from the mold and the surface was rinsed with deionized water, and then freeze-dried at -40°C for 12 h to obtain alginate aerogel.
[0052] (3) The aerogel was heated in N 2 After calcination at 500°C for 10 hours in an ambient environment, alginate aerogel with a porous three-dimensional structure was obtained after carbonization.
[0053] (4) Take 0.5g of titanium dioxide P25 and add it to 100mL of sodium hydroxide solution with a concentration of 10mol / L and mix them evenly. Pour the mixed solution and the carbonized aerogel into a hydrothermal reactor. Place the hydrothermal reactor in a constant temperature oil bath and react at 150°C for 24h. Rinse it twice with 0.1mol / L dilute nitric acid, rinse it three times with deionized water, and then dry it at 80°C for 12h to obtain a photoelectric coupling catalytic material.
[0054] The catalytic material is placed as follows: the photoelectric coupling catalytic material is placed in a photoelectric coupling reactor as an anode material, with the titanium dioxide surface facing the ultraviolet light, and 1L of high-salt organic wastewater with a salinity of 40ppt and a COD content of 5000mg / L is added to the reactor. The power of the photoelectric coupling reactor is turned on, and the reaction is carried out for 60 minutes. The water sample is taken out to detect the remaining COD content and salinity changes.
[0055] Comparative experiment 1:
[0056] When there is no photoelectric coupling catalytic material, add 1L of high-salt organic wastewater with a salinity of 40ppt and a COD content of 5000mg / L into the photoelectric coupling reactor, turn on the power of the photoelectric coupling reactor, react for 60 minutes, and take out the water sample to detect the remaining COD content and salinity changes.
[0057] Comparative experiment 2:
[0058] Using the photoelectric coupling catalytic material prepared in Example 3, 1 L of high-salt organic wastewater with a salinity of 40 ppt and a COD content of 5000 mg / L was added to the photoelectric coupling reactor. The power of the photoelectric coupling reactor was turned on without ultraviolet light. The reaction was carried out for 60 minutes, and the water sample was taken out to detect the remaining COD content and salinity changes.
[0059] Comparative experiment 3:
[0060] Using the photoelectric coupled catalytic material prepared in Example 3, 1 L of high-salt organic wastewater with a salinity of 40 ppt and a COD content of 5000 mg / L was added to a photoelectric coupled reactor. The reaction was carried out for 60 minutes under ultraviolet light conditions alone, and the water samples were taken out to detect the remaining COD content and salinity changes.
Claims
1. A method for preparing a material having photoelectric coupled catalytic performance, characterized in that: The preparation steps are as follows: S1, preparing alginate aqueous solution; S2, preparing a zinc salt solution and an iron salt solution, and mixing the two to form a precursor solution; S3, mixing the prepared alginate aqueous solution and the precursor solution evenly, and letting them stand to obtain a cross-linked alginate hydrogel; S4, washing the surface of alginate hydrogel and freeze-drying to obtain alginate aerogel; S5, calcining the alginate aerogel at a high temperature in a nitrogen, argon or neon atmosphere to obtain a carbonized alginate aerogel; S6, loading TiO2 modified by hydrothermal method onto the surface of carbonized alginate aerogel; S7, washing the material obtained in the previous step with a dilute acid solution, and then washing with water and drying to obtain the material having photoelectric coupling catalytic performance.
2. The preparation method according to claim 1, characterized in that: The weight percentage of the alginate aqueous solution is 2wt% to 5wt%.
3. The preparation method according to claim 1, characterized in that: The alginate includes sodium alginate, potassium alginate, calcium alginate or magnesium alginate; wherein, when the zinc salt and the iron salt described in S2 are sulfates, calcium alginate cannot be used as the alginate.
4. The preparation method according to claim 1, characterized in that: The zinc salt solution and the iron salt solution described in step S2 include zinc nitrate solution and ferric nitrate solution, zinc chloride solution and ferric chloride solution, zinc sulfate solution and ferric sulfate solution, and zinc acetate solution and ferric acetate solution. The dilute acid solution described in step S7 includes dilute nitric acid, dilute hydrochloric acid, dilute sulfuric acid or dilute acetic acid, corresponding to the anion types of the zinc salt solution and the iron salt solution described in step S2.
5. The preparation method according to claim 1, characterized in that: The precursor solution is prepared by mixing a zinc salt solution with a molar concentration of 0.03-0.06 mol / L and an iron salt solution with a molar concentration of 0.03-0.06 mol / L in a volume ratio of 1:5-5:
1.
6. The preparation method according to claim 1, characterized in that: The specific steps of hydrothermal modification of TiO2 are: adding TiO2 to a sodium hydroxide solution with a molar concentration of 10-20 mol / L and mixing evenly, then pouring the mixed solution and the carbonized aerogel into a hydrothermal reactor and reacting at 150-200°C for 24-48 hours.
7. The preparation method according to claim 1, characterized in that: The TiO2 added is titanium dioxide P25, and the amount added is 3-10g / L.
8. A material obtained by the preparation method according to claims 1 to 7.
9. Use of a material as claimed in claim 8, characterized in that: It is used to treat organic pollutants in wastewater.
10. The use according to claims 7 to 8, characterized in that: The material is placed in a photoelectric coupled catalytic reactor as an anode electrode to treat high-salt organic dye wastewater; this material as an anode electrode can remove organic pollutants in water through photocatalytic oxidation, and can also degrade organic pollutants in water through electrochemical oxidation.
Citation Information
Patent Citations
Method for preparing BDD-TiO2 pole with P-N junction characteristic
CN101555050A
Preparation method and application of titanium dioxide / carbon aerogel photocathode
CN107268014A
Catalyst for pollutant degradation under natural light and preparation method of catalyst
CN112452320A
Preparation method of CeO2-TiO2 composite aerogel for photocatalytic reduction of CO2
CN114054013A
Preparation method and application of TiO2 / MXene heterojunction composite aerogel
CN114959744A